Ex-Post and Ex-Ante Forecasts of Spot Prices in Bulk Shipping in a Period of Economic Crisis using Simultaneous Equation Models - Nikolaos D. Geomelos; Evangelos Xideas (SPOUDAI - Journal of Economics and Business, 2014)
The paper deals with forecasting of spot prices in bulk shipping using simultaneous equations models (SEMs) during the present economic crisis, emphasizing the importance of such models in empirical applied economics and for decision-makers. The SEMs predictive performance on the spot market is estimated for a selection of eight main vessel categories, five in the tanker market and three in the dry bulk market. SEMs take into account feedback loops between the spot market and its environment. SEMs are considered more complete models as spot prices and variables such as time-charter rates, fleet deadweight capacity and prices of second-hand, newbuilding and scrap markets are determined simultaneously by the shipping markets' operation. This approach enables estimating 29 different systems for each vessel type, generated by the combination of the aforementioned variables. The research sample period consists of an initialization data subset (1970:01-2010:02), of a subset for ex-post forecast (2010:03-2011:02) and a subset for ex-ante forecasts (2011:03-2012:02) employing monthly time series. Results reveal that simultaneous estimation of endogenous variables is described by precision and rationality while the t-tests show that exogenous variables are characterized by very high statistical significance. The out-of-sample forecasts show that SEMs provide useful information about market turning points.
Keywords: C53; C32; E32; 330; econometric methodology; simultaneous equations models; spot prices; ex-post and ex-ante forecasts; forecasting uncertainty